Incretin based therapies - Kalra, Sanjay; Sahay, Rakesh; Unnikrishnan, Ambika G. (India : Jaypee Brothers Medical Publishers, 2013)
Multiple pharmacotherapeutic agents are now used in diabetology practice. The sheer scale of the permutations and combinations sometimes leaves practitioners confused as to their appropriate use. The major recent advance in diabetic drug therapy has been the development of incretin based therapies. These agents of varying chemical structures have changed our approach to diabetes care, bringing with them an enhanced understanding of the pathophysiology and natural history of the disease. However, they also bring with them a challenge for the diabetes care professional. Confronted with a wide choice of "newer" drugs, the diabetes care provider feels the need for more information to write a rational prescription. This book fulfills this need. An easily readable and comprehensible lay out helps make complicated concepts look simple. Classification of incretin based therapy into different groups, each discussed separately, gives the reader clarity. For each group, an overview chapter is followed by a focused discussion of various aspects of clinical pharmacology. While a section on the history and developments of incretin based therapy puts this novel class of drugs in perspective, futuristic chapters on nondiabetic usage and combination therapy give a glimpse of their untapped potential.
Section 1: Incretins: An Introduction Section 2: Clinical Pharmacology of GLP-1 Analogues Section 3: Clinical Pharmacology of DPP-4 Inhibitors Section 4: Pleiotropic Effects of Incretins Section 5: Comparative Pharmacology
Incluye ilustraciones
Incluye índice
Incluye bibliografía
Keywords: INCRETINAS; THERAPIES